La era digital de la radio - Rivadeneyra Olcese, Carlos Vidal (2012)
The radio, the very first electric mean of massive communication goes through technological changes facing new digital production processes and distribution of contents. These changes can be highlighted throughout the strategy used on the creation of audible content as well as on how it is accessed and consumed by users. Social sensitivity and practices on the digital radio scene are much different to the ones used on an earlier era. Thus, we propose understanding today as a moment of mutation for this media, a moment in which the digital era of the radio begins.